A review of quality engineering tools and techniques practices in Malaysia's and Indonesia's automotive industries and an agenda for future research - Tri Putri, Nilda; Mohd. Yusof, Sha'ri (2008)

(untitled)
Studies of Quality Engineering (QE) usually focused on the areas of process control tools in production and improvement tools used to improve existing production processes and its title typically covers such as Statistical Process Control (SPC), Taguchi Methods and Design of Experiment. Only a few studies that looks into a comprehensive implementation of QE Tools and Techniques especially in Malaysia and Indonesia automotive industries. This paper aims to review the QE tools and techniques practices of Malaysia and Indonesia Automotive Industries in their quality improvement efforts. This paper also highlights the importance of implementation of QE tools and techniques in company in various countries and the problems encountered when using QE tools and techniques found in the literature. The further research will identify and evaluate the critical success factors for the successful implementation of QE. The Analytic Hierarchy Process (AHP) approach is going to be employed to prioritize the critical factors for implementing QE. The AHP approach is used in this study because it can help researchers to formulate an appropriate model to evaluate critical success factors and develop strategies to implement QE tools and techniques in Malaysia and Indonesia automotive industries. Furthermore, it is believed that the developing of conceptual model will need for successful QE practices in Malaysia and Indonesia automotive industries based on empirical research.